2011
DOI: 10.1083/jcb.201006089
|View full text |Cite
|
Sign up to set email alerts
|

c-Jun N-terminal kinase phosphorylates DCP1a to control formation of P bodies

Abstract: JNK-mediated phosphorylation of the mRNA-decapping protein DCP1a disrupts P body structure, mRNA stability, and gene expression in response to stress and inflammatory stimuli.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
93
1
1

Year Published

2013
2013
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(101 citation statements)
references
References 56 publications
(110 reference statements)
6
93
1
1
Order By: Relevance
“…52,53 O-linked N-acetyl glucosamine, 53 poly (ADP) ribosylation, 54 acetylation, and ubiqutination 39 are also modifications present on specific stress granule components, which have been implicated in stress granule assembly, albeit the mechanisms are not entirely clear. Finally, the phosphorylation of several proteins, including G3BP, 29 TTP, 55 Dcp1, 42,56 Dcp2, 57 and 4E-T 58 alters their localization within, and/or the assembly of their respective granules. In addition, phosphorylation in the prion-like domain of FUS impairs hydrogel formation in vitro.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
“…52,53 O-linked N-acetyl glucosamine, 53 poly (ADP) ribosylation, 54 acetylation, and ubiqutination 39 are also modifications present on specific stress granule components, which have been implicated in stress granule assembly, albeit the mechanisms are not entirely clear. Finally, the phosphorylation of several proteins, including G3BP, 29 TTP, 55 Dcp1, 42,56 Dcp2, 57 and 4E-T 58 alters their localization within, and/or the assembly of their respective granules. In addition, phosphorylation in the prion-like domain of FUS impairs hydrogel formation in vitro.…”
Section: Mrnp Granules Assemble Via Common Mechanismsmentioning
confidence: 99%
“…Dcp1a in P-bodies constantly and quickly exchanges with Dcp1a in the cytoplasmic pool during fluorescence recovery after photobleaching analysis (34). Phosphorylation at Ser-315 mediates Dcp1a release from P-bodies as well as the regulation of P-body formation during translational stress (32), which suggests that Dcp1a may be involved in modulation of, or signal transduction from, P-bodies. In contrast, Dcp2 has a slower recovery rate during fluorescence recovery after photobleaching experiments, suggesting that it is a core P-body protein (34).…”
mentioning
confidence: 99%
“…Previous studies have indicated roles for Dcp1a in P-body formation, maintenance, and regulation (6,32,33). Dcp1a in P-bodies constantly and quickly exchanges with Dcp1a in the cytoplasmic pool during fluorescence recovery after photobleaching analysis (34).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have pinpointed phosphorylation of PB resident proteins as key to the control of their assembly. [60][61][62] For example, the direct phosphorylation of PB scaffolding protein Pat1 by cAMP-dependent protein kinase PKA causes PB dissolution and reduces cell survival in times of stress. 60 Similarly, several viruses have been shown to accelerate the decay of PB resident proteins, or recruit PB resident proteins to viral replication compartments to enhance replication.…”
Section: Modelmentioning
confidence: 99%